2010
DOI: 10.1080/01457631003639067
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Analysis for a Concentric Tube Heat Exchanger Including the Wall Axial Conduction

Abstract: The effect of wall axial conduction on the heat transfer in a concentric tube heat exchanger is examined for the inner flow laminar flow regime. The procedure used for the current analysis combines the analytical solution for the inner fluid with a numerical approximation for the wall conduction and has the capability of handling the temperature variation for the outer fluid. Both parallel and counterflow cases are evaluated for the analysis, and results are presented in terms of the axial variations of fluids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Arici [12] examined the conjugate heat transfer of both parallel-flow and counter-flow concentric tube heat exchangers. The numerical results indicated that the effect of LHC was non-negligible only for counter-flow conditions especially for low heat capacity ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Arici [12] examined the conjugate heat transfer of both parallel-flow and counter-flow concentric tube heat exchangers. The numerical results indicated that the effect of LHC was non-negligible only for counter-flow conditions especially for low heat capacity ratio.…”
Section: Introductionmentioning
confidence: 99%